An Exploration of EFL Young Leaners’ Speaking Difficulties Faced by the Sixth Grade Students of Elementary School - Dairobi, Ahmad; Mubarok, Tyas Alhim; Widiarini, Widiarini (UIBU, 2025)
This study explores students’ approaches to learning English speaking, the difficulties they face, and the strategies teachers use to overcome them. A qualitative approach with a case study was used to reach the aims of the research. The data collection techniques involved observation at the research location, which is MI Nurul Islam Bululawang; interviews with relevant parties, specifically the sixth-grade students, comprising 16 students, and the English teacher of that class; and documentation to strengthen the findings of this study. The data analysis was conducted through four main stages: data collection, data reduction, data display, and conclusion drawing. The findings indicate that English language instruction is already running smoothly and effectively, but some difficulties are still found in the learning process, including difficulties in speaking English and a lack of interest and enthusiasm during the process. There have also been several efforts made by the teacher and the school to overcome the difficulties experienced by the students, namely by providing support and motivation to the students and offering extra hours for studying English.